PREOPERATIVE MORTALITY SCORES IN RUPTURED ANEURYSMS — BIBLIOGRAPHIC REVIEW - Oliveira-Pinto, José (2017)
Ruptured Abdominal Aortic Aneurysms present with significant lethality, long hospitalization periods at intensive care units and elevated health costs. Aneurysm-related mortality is highly dependent on the clinical state and physiological reserve of the patient previous to the surgery. In order to stratify which factors may condition mortality and to understand the best candidates for surgical treatment, several scores have been published with dozens of analyzed variables. The most relevant scores are: Glasgow Aneurysm Score, Vancouver Scoring System, Hardman Index, Edinburgh Rupture Aneurysm Score (ERAS) e Vascular Study Group of New England (VSGNE). This review intends to summarize the most relevant findings and to provide a critical analysis of each aneurysm score.